Implementation of Wordwall Media with a STEM Approach to Increase Student Creativity and Learning Outcomes in Chemical Compound Nomenclature - Maria Alex Sandra; Fauzan Adhim; Rina Sugiarti Dwi Gita (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to examine the effect of integrating Wordwall media with the STEM approach on student creativity and learning outcomes in chemical compound nomenclature. A quasi-experimental method with a Pretest-Posttest Control Group design was applied. The experimental group used STEM-based Wordwall media, while the control group received conventional teaching. Results showed that the experimental group achieved a moderate N-Gain (0.66) compared to the control group’s lower N-Gain (0.29). The Mann-Whitney test indicated a significant difference between the groups (p < 0.05), suggesting that STEM-based Wordwall media improved learning outcomes. Creativity, measured using a Torrance-based questionnaire, also showed significant improvement after the intervention. In conclusion, integrating Wordwall media with the STEM approach effectively enhances student creativity and learning outcomes in chemical compound nomenclature.